SH-1028, An Irreversible Third-Generation EGFR TKI, Overcomes T790M-Mediated Resistance in Non-Small Cell Lung Cancer - Han, Luwei; Zhang, Xiaomeng; Wang, Zhiqiang; Zhang, Xian; Zhao, Liwen; Fu, Wei; Liang, Xiaobo; Zhang, Zhibo; Wang, Yong (Frontiers in Pharmacology, 2021)
SH-1028 is an irreversible third-generation EGFR TKI. Both SH-1028 and osimertinib have a pyrimidine structure (a typical mutant-selective EGFR TKI structure). Compared with osimertinib, SH-1028 is modified on the indole ring, thus resulting in a more stable 6,7,8,9-tetrahydro-pyrrolo [1, 2-a] indol structure. In this study, we explored the anti-tumer effect of SH-1028 in cells and xenograft models, the inhibition of cell signal, such as EGFR and ERK phosphorylation, and verified the relationship between the pharmacokinetics and pharmacodynamic responses. In the present study, SH-1028 selectively inhibited EGFR sensitive and resistant mutations, with up to 198-fold more effective compared with wild-type EGFR cells. In mouse xenograft models, oral administration of SH-1028 at a daily dose of 5 mg/kg significantly inhibited tumor cells with EGFR sensitive mutation (exon 19 del) and resistant mutation (T790M) for consecutive 14 days, with no TKI-induced weight loss. SH-1028 exhibited good bioavailability, and was distributed extensively from the plasma to the tissues. The main metabolite of SH-1028, Imp3, was tested and showed no wild-type EGFR inhibition or off-target effects. In conclusion, SH-1028 is a new third-generation EGFR inhibitor that exhibits potent activity against EGFR sensitive and resistant (T790M) mutations.